2011
DOI: 10.1532/hsf98.20101119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Uniatrial and Biatrial Radiofrequency Ablation Procedures in Atrial Fibrillation: Initial Results

Abstract: Biatrial ablation surgical procedures were more effective in controlling atrial fibrillation than procedures limited to the left atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…In 10 studies (35.7%) mitral surgery was the main procedure performed in association with AF ablation, while in the remaining studies various types of main procedures (coronary surgery, valve surgery, aortic surgery, etc) were performed aside of AF ablation. Four studies enrolled only patients rheumatic valve disease (RVD) in both study groups, while 4 more studies reported a variable quota of RVD ranging between 50% and 70% of the population, while in the remaining 20 studies the incidence of RVD was not clearly stated.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 10 studies (35.7%) mitral surgery was the main procedure performed in association with AF ablation, while in the remaining studies various types of main procedures (coronary surgery, valve surgery, aortic surgery, etc) were performed aside of AF ablation. Four studies enrolled only patients rheumatic valve disease (RVD) in both study groups, while 4 more studies reported a variable quota of RVD ranging between 50% and 70% of the population, while in the remaining 20 studies the incidence of RVD was not clearly stated.…”
Section: Resultsmentioning
confidence: 99%
“…23,35,36 Ten (35.7%) were prospective observational studies, of which two had propensity adjustment. 3,4,21,22,24,25,27,31,32,37 The remaining 15 studies (53.6%) were retrospective observational, of which 3 were propensity adjusted. 5,19,20,26,[28][29][30]33,34,38,39,[44][45][46][47] In 16 studies (57.1%) all the patients enrolled presented exclusively non-paroxysmal AF forms and these studies constituted the "non-paroxysmal AF subgroup."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations